The roles of mandarin fish STING in innate immune defense against Infectious spleen and kidney necrosis virus infections. Issue 100 (May 2020) - Qin, Xiao-Wei; He, Jian; Yu, Yang; Liu, Chang; Luo, Zhi-Yong; Li, Zhi-Min; Weng, Shao-Ping; Guo, Chang-Jun; He, Jian-Guo
Abstract: The mandarin fish Siniperca chuatsi is a cultured freshwater fish species that is popular in China because of its high market value. With the development of high-density cultural mode in mandarin fish, viral diseases such as Infectious spleen and kidney necrosis virus (ISKNV) are becoming increasingly serious. Stimulator of interferon genes (STING) is a central component in the innate immune response to cytosolic DNA and RNA derived from different pathogens. However, the roles of STING in innate immune response of mandarin fish remain unknown. In the present study, S . chuatsi STING ( sc STING)-mediated host immune response against ISKNV infection was investigated. Sc STING transcription level increased remarkably in response to ISKNV infection, LPS, PMA, or poly (I:C) stimulation in mandarin fish fry (MFF-1) cells. Immunofluorescence results showed that sc STING localized majorly in the endoplasmic reticulum. sc STING overexpression remarkably increased the expression levels of scIFN-h, scMx, scISG15, scPKR, scViperin, scIL-1β, scIL-18, and scTNF-α genes. IFN-β-luciferase report assay results showed that the relative expressions of luciferin were remarkably increased in MFF-1 cells. Site mutation of serine (S) on C-terminus of sc STING showed that both S388 and S396 were important for mediated signaling. Furthermore, sc STING overexpression inhibited ISKNV infection, and knockdown of sc STING promoted ISKNV infection, indicating that sc STING could suppress ISKNV infection in MFF-1 cells. These observations suggested that the sc STING played an important role in innate immune against ISKNV infection. Our work would help elucidate the roles of teleost fish STING in innate immunity. Highlights: sc STING can evoke interferon and inflammatory immune responses. The Ser388 and Ser396 sites are crucial for sc STING-mediated signaling. sc STING mediates host antiviral immune response against ISKNV infection.